2014
DOI: 10.1097/mao.0000000000000587
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence of Preauricular Sinus and Associated Factors in a Nationwide Population-Based Survey of South Korea

Abstract: A large-scale government-centered survey demonstrates a high prevalence, female dominance, and age-related decrease of PAS in South Korea.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 13 publications
1
10
0
1
Order By: Relevance
“…The reported incidence figures in our study are similar to others reported in European and Caucasian populations, somewhat underlining the genetic predispositions on inheritance, as the reported figures in Asian and African populations are significantly higher (11,14,20,22).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The reported incidence figures in our study are similar to others reported in European and Caucasian populations, somewhat underlining the genetic predispositions on inheritance, as the reported figures in Asian and African populations are significantly higher (11,14,20,22).…”
Section: Discussionsupporting
confidence: 91%
“…A structure was considered a PAuS when present in the region of the crus of the auricular helix as a preexisting dent, dimple or foramen, not due to an ear piercing, other cosmetic or medical procedures. The set criteria were virtually identical to similar studies of the structure, carried out in other cohorts (10)(11)(12)22).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Although can present as an infected and discharging sinus associated with abscess formation and can easily be misdiagnosed as a sebaceous cyst or a furunculus. [4][5][6] Preauricular sinus are prone to recurrent infection mainly by Staphylococcus aureus organism and usually presents with an intense irritation, pain, swelling/oedema, ear discharge, fever, headache and when the sinus punctum is blocked pus accumulates leading to abscess formation. Surgical intervention becomes an absolute option once the sinus gets infected and this will reduce recurrence, the incidence been reported to be 19-40%.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical intervention becomes an absolute option once the sinus gets infected and this will reduce recurrence, the incidence been reported to be 19-40%. 4 Surgical drainage is necessary in the acute phase where abscess is present with institution of appropriate sensitive antibiotics. 2,[5][6][7] There is dearth of medical literature on preauricular sinus abscess in our region as obtained in other parts of the world.…”
Section: Introductionmentioning
confidence: 99%